Acute coronary syndrome after liver transplantation in a young primary biliary cholangitis recipient with dyslipidemia: a case report - Siyuan Yao; Akiho Iwashita; Shintaro Yagi; Hirotoshi Watanabe; Takahiro Nishio; Yukinori Koyama; Kazuyuki Nagai; Naoko Kamo; Kojiro Taura; Etsuro Hatano (Surgical Case Reports, 2022)
Abstract Background Primary biliary cholangitis (PBC) is a chronic, progressive liver disease associated with dyslipidemia. There is a consensus that PBC does not accelerate coronary artery disease despite high cholesterol levels, so the screening test for the coronary artery is not routinely performed before liver transplantation (LT). To date, no report has described the potential risk of PBC-related dyslipidemia for developing acute coronary syndrome (ACS) after LT. Case presentation A 40-year-old Asian female with a known history of PBC underwent ABO-incompatible living-donor LT, with her husband as the donor. Although she had high cholesterol and triglyceride levels that were refractory to medications, she passed all routine preoperative examinations, including cardiopulmonary function tests and infection screenings. One week after LT, she developed ACS with 90% stenosis of both the left anterior descending artery and left circumflex artery. Emergent stent implantation was successfully performed followed by dual antiplatelet therapy. The long history of PBC and associated severe dyslipidemia for 10 years would have accelerated the atherosclerosis, causing latent stenosis in the coronary artery. Inapparent stenosis might have become apparent due to unstable hemodynamics during the acute phase after LT. Conclusions PBC-related dyslipidemia potentially brings a risk for developing ACS after LT. This experience suggests that the preoperative evaluation of the coronary artery should be considered for high-risk patients, especially those who have drug-resistant dyslipidemia.